Relationships Between Body Mass Index, Allogeneic Transfusion, and Surgical Site Infection After Knee and Hip Arthroplasty Surgery. (7th April 2022) - Tanaka, Kenichi A.; Pontikes, Andrew E.; Van, David; Vandyck, Kofi; Butt, Amir; Mazzeffi, Michael A.; Thakral, Rishi; Stewart, Kenneth E.
Abstract : BACKGROUND: Increased body mass index (BMI) is considered as an important factor that affects the need for total knee and hip arthroplasty (TKA/THA) and the rate of perioperative complications. Previous investigations have not fully established the relationship of BMI and perioperative transfusion with surgical site infection (SSI) or the relationship of BMI and perioperative transfusion after TKA or THA. METHODS: The National Surgical Quality Improvement Program database was used to perform a retrospective cohort study involving 333, 223 TKA and 41, 157 THA cases between 2011 and 2018. Multivariable regression assessed the associations of BMI (5 standard categories) and transfusion with SSI. Odds ratio (OR) of SSI was calculated relative to a normal BMI (18.5–24.9 kg/m 2 ) after adjustment of potential confounding factors. RESULTS: Perioperative transfusion decreased significantly over time for both TKA and THA; however, SSI rates remained steady at just under 1% for TKA and 3% for THA. In TKA, a higher OR for SSI was associated only with a BMI of 40+ (OR, 1.86; 95% confidence interval [CI], 1.60–2.18) compared to a referent BMI. In THA, increased ORs of SSI were seen for all BMI levels above normal and were highest for a BMI 40+ (OR, 3.08; 95% CI, 2.47–3.83). In TKA, ORs of transfusion decreased with increasing BMI and were lowest for a BMI 40+ (OR, 0.51; 95% CI, 0.47–0.54). In THA, ORs of transfusion began to increase slightly in overweight patients, reaching an OR of 1.36 (95% CI, 1.21–1.54) for a BMI 40+. CONCLUSIONS: SSI incidence remained unchanged despite continuous reductions in blood transfusion in TKA and THA patients over 8 years. In TKA, ORs for SSI increased, but ORs for transfusion decreased with increasing BMI above normal. Conversely, in THA, ORs for SSI and transfusion both increased for a BMI 40+, but only OR for transfusion increased in underweight patients. These findings suggest the importance of controlling obesity in reducing SSI following TKA and THA.